2017
DOI: 10.1038/ncomms15534
|View full text |Cite
|
Sign up to set email alerts
|

USP13 negatively regulates antiviral responses by deubiquitinating STING

Abstract: STING (also known as MITA) is critical for host defence against viruses and the activity of STING is regulated by ubiquitination. However, the deubiquitination of STING is not fully understood. Here, we show that ubiquitin-specific protease 13 (USP13) is a STING-interacting protein that catalyses deubiquitination of STING. Knockdown or knockout of USP13 potentiates activation of IRF3 and NF-κB and expression of downstream genes after HSV-1 infection or transfection of DNA ligands. USP13 deficiency results in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
131
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(134 citation statements)
references
References 39 publications
0
131
0
Order By: Relevance
“…22,23 Although around a half dozen E3s have been reported to catalyze K48-linked ubiquitination and degradation of MAVS, it remained unknown how deubiquitination of MAVS is regulated and whether such a regulation modulates innate immune responses against RNA viruses. Through an unbiased screening by cotransfection and immunoprecipitation assays that we have previously established, 44,45 we identified OTUD4 as a MAVS-interacting DUB ( Fig. 1 and Supplementary information, Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 Although around a half dozen E3s have been reported to catalyze K48-linked ubiquitination and degradation of MAVS, it remained unknown how deubiquitination of MAVS is regulated and whether such a regulation modulates innate immune responses against RNA viruses. Through an unbiased screening by cotransfection and immunoprecipitation assays that we have previously established, 44,45 we identified OTUD4 as a MAVS-interacting DUB ( Fig. 1 and Supplementary information, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To test this hypothesis, we screened for DUBs that interact with MAVS by cotransfecting individual FLAG-tagged DUBs and HA-MAVS into HEK293 cells followed by coimmunoprecipitation and immunoblot assays. 44,45 This led to the identification of multiple DUBs that interacted with MAVS, including OTUD4, CYLD and USP35 ( Fig. 1a and Supplementary information, Fig.…”
Section: Identification Of Otud4 As a Mavs-interacting Dubmentioning
confidence: 99%
“…Typical K48-and K63-linked ubiquitination have been extensively characterized, whereas research about other ubiquitination types remains relatively elusive. In recent years, some studies have reported that other ubiquitination types are responsible for the immunoregulation mediated by MAVS and MITA (45,46). Interestingly, an increasing number of investigations proved that there is crosstalk between the ubiquitin-proteasome and autophagy-lysosome systems, suggesting the emerging roles of ubiquitin and ubiquitin-binding proteins in selective autophagy (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, A20 can also bind to specific E2 enzymes and induce their degradation as a mechanism to prevent ubiquitination of other proteins [54]. Several more DUBs that play a role in the regulation of the immune response have been identified such as OTU DUBs Cezanne, OTULIN, and UPS DUBs USP3, 13, and 21 [7,[55][56][57][58]. Mutations in genes encoding DUBs involved in negative regulation of innate immune signaling, like CYLD and A20, can lead to the development of diseases including cancer and autoimmune and inflammatory disorders, highlighting the importance of DUB-controlled immune signaling [59,60].…”
Section: Antiviral Innate Immune Response and Its Regulation By Ubmentioning
confidence: 99%